Students’ Perception of Professional Accountant Skills and Knowledge - Palacio-Fierro, Andrés (2024)
In response to the constant changes caused by globalization, the business sector has considered it very important that the training presented by accountants not only focus on technical skills, but also, generic, or soft skills are developed, which allow accounting professionals to face the challenges posed by competitiveness. The purpose of the study is to carry out an analysis of the perception that students show about the skills and knowledge that the professional accountant needs. A questionnaire with the different skills and knowledge that an accountant must possess was applied to the seventh and eighth semester students. Likewise, for the treatment of the data, a factorial analysis was applied. The data obtained show that the students of the Accounting Career consider that for their good performance they require training in both knowledge and practical skills. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2